2016
DOI: 10.4067/s0717-95022016000400041
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anatomy Education in Facilitating Multidisciplinary Collaboration in the Treatment of Musculoskeletal Conditions ­ an Example from Australia

Abstract: SUMMARY:Emerging changes to the healthcare system are promoting the adoption of an integrative medicine and a more patient-centred approach to healthcare. A multidisciplinary approach to the management of musculoskeletal conditions has a potential to ease the pressure off the emergency public health care system. Interprofessional collaboration in health care is paramount for this synergism to occur. It is crucial that treatment options be consistent and transparent across different health professions in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The survey demonstrated that in the anatomy-only courses required for the chiropractic qualification in Australia, chiropractic students were not always the majority of the cohort (range: 29% [Institution 1] to 85% [Institution 4)]). Notwithstanding, this presents a challenge to customizing the content delivery, and while it is unclear whether this is an intentional effort to develop interdisciplinary collaborative learning communities, it can be argued that anatomy presents the earliest opportunity to embed inter-disciplinary team learning (Giuriato et al, 2016). This opportunity can be utilized to enhance skills such as communication, which will be required in clinical practice post-graduation (McBride and Drake, 2015) as well as provide opportunities to develop an awareness of interprofessional teamwork which can impact later professional collaboration (Jones, 2010;Pawlina and Drake, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The survey demonstrated that in the anatomy-only courses required for the chiropractic qualification in Australia, chiropractic students were not always the majority of the cohort (range: 29% [Institution 1] to 85% [Institution 4)]). Notwithstanding, this presents a challenge to customizing the content delivery, and while it is unclear whether this is an intentional effort to develop interdisciplinary collaborative learning communities, it can be argued that anatomy presents the earliest opportunity to embed inter-disciplinary team learning (Giuriato et al, 2016). This opportunity can be utilized to enhance skills such as communication, which will be required in clinical practice post-graduation (McBride and Drake, 2015) as well as provide opportunities to develop an awareness of interprofessional teamwork which can impact later professional collaboration (Jones, 2010;Pawlina and Drake, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Empowering health professionals with a range of diverse skills and competencies required by the fast‐evolving medical practice has been a mark of modern medical education (Giuriato et al, 2016; Bandiera et al, 2018; McBride and Drake, 2018). Continuous discoveries in medicine and appreciation of diverse healthcare needs in recent years, have had a ripple effect throughout medical curricula including the subject of anatomy (McBride and Drake, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been published, which strongly suggest that medical and allied health students and practitionersview anatomy as one of the most important preclinical subjects (Pabst & Rothkötter, 1997;Moxham & Plaisant, 2007;Lazarus et al, 2012;Plaisant et al, 2014;Strkalj et al, 2014). A thorough understanding of anatomy is vital to clinical practice; in the accurate diagnosis of conditions, in the selection and performance of safe and effective treatment interventions, and in facilitating inter-professional communication (Turney;Plaisant et al;Estai & Bunt;Giuriato et al, 2016).…”
Section: Introductionmentioning
confidence: 99%